Gamma Radiolysis Studies of Aqueous Solution of Brilliant Green Dye - D. V. Parwate; S. S. Mankar (E-Journal of Chemistry)
The effect of γ–radiation on colour intensity of aqueous solution of Brilliant Green has been investigated at two different concentrations. The degradation of Brilliant Green (BG) has also been investigated in presence of suspended ZnO, by adding different amounts of ZnO. Simultaneously the conductance and pH of each solution system were measured before and after γ-irradiation. All the γ–irradiations were performed at a dose rate of 0.60 kGyhr-1 in GC-900. The maximum dose required for the complete degradation of the dye was found to be 0.39 kGy. G(-dye) values were found to decrease with increase in gamma dose and were in the range 4.26 - 12.81. The conductance (7.6 - 25.3 μS) and pH values increased marginally with dose for both the concentrations. The rate of decolouration was found to be high at lower doses and the efficiency of dye removal was higher at low concentration of the dye. This may be attributed to the presence of reaction by-products from the destruction of parent compound build up and compete for reaction intermediate species. The rate of reaction and rate constants were calculated and it was found that the degradation reaction follows first order kinetics. It was found that the decolouration percentage was more in dye systems in absence of ZnO.